Crystal structure of dimethanol-bis{3-(((2-oxidonaphthalen-1-yl)methylene)amino)-2-oxo-2H-chromen-4-olato-κ3O,N:O′}dizinc(II), C42H30Zn2N2O10 - Su Qiong (Zeitschrift für Kristallographie - New Crystal Structures, 2018)
C42H30Zn2N2O10, monoclinic, P21/c (no. 14), a = 8.5451(9) Å, b = 11.6897(12) Å, c = 18.4893(19) Å, β = 100.733(3)°, Z = 2, V = 1814.6(3) Å3, Rgt(F) = 0.0404, wRref(F2) = 0.1029, T = 296(2) K.